Japan, and Its Pacifism : A Choice Amid the Rise of China and the Widening of North Korea - Pertiwi, Annisa Dipa (Universitas Perrtahanan Indonesia (UNHAN), 2021)
This research is about interpretation picture given by the lecturer of foreign policy analysis about Japan pacifism in between of China and North Korea. The central research-problem focuses on the factors that how Japan facing the security challange amid to real threats between the raise of China and the Widening of Nuclear from North Korea, that will affects a state’s foreign policy decision in the field of security, power stucture through defense procurement. This research is build by foreign policy analysis concept, also the rational choice approach. The result shows that the output that will be obtained from the changing of foreign policy will make it easier for Japan to take a part in bilateral and multilateral military exercise with countries other than the United States, including Southeast Asia countries such as the Philippines which has maritime disputes with China and welcoming Japan’s expanded security role.